Copyright Reform and Fact-Based Works - Scassa, Teresa (Université d'Ottawa | University of Ottawa, 2010)
In recent years we have seen a dramatic growth in the number of websites, databases, tools and applications which use data from a variety of public and private sources to offer innovative information-based services to a wide range of users. In many cases, the innovators are upstarts – individuals or small companies that see opportunities for new and useful applications. Although developers may rely upon the copyright doctrine that there is no copyright in facts when they create their tools, the state of the law in this area reveals many uncertainties. In an innovation economy, clarity around the status and use of data in new works is crucial; and the public interest is best served by facts remaining in the public domain. This chapter provides an overview of the current state of the law in relation to the protection of fact-based works in copyright law. It then considers the extent to which Bill C-32 clarifies, ignores or makes worse the state of the law in this area.
Keywords: facts; intellectual property; compilations; copyright